An innovative mooring system for floating storage tanks and stochastic dynamic response analysis. (15th December 2018) - Wan, Ling; Zhang, Chi; Magee, Allan Ross; Jin, Jingzhe; Han, Mengmeng; Ang, Kok Keng; Hellan, Øyvind
Abstract: A modular floating concept for oil storage is proposed. The concept is composed of modular floating tanks and barges. The floating tanks are self-stable and designed for storage of oil and hydrocarbon material. The barges are connected together and moored by mooring dolphins. Mooring system is designed between barges and the tanks enclosed by the barges. An innovative mooring system that consists of several mooring ropes besides the fender system is proposed and investigated in this study. The mooring ropes are stretchy and can carry the mooring loads in all the loading and environmental conditions. Single floating tank is investigated under different filling levels, i.e. empty, full and partially filled conditions. It is assumed in this study that the barges are fixed, and multi-body hydrodynamic interaction is neglected. Linear and nonlinear mooring rope properties are investigated. Failure condition of one of the mooring rope is also considered. Wind, wave and current load effects under 100-year storm are also investigated, as well as the uncertainty analysis in terms of viscous effects. Highlights: Dynamic response analysis of floating storage tanks, under operational and extreme conditions. Innovative mooring system design and analysis for the floating storage tanks. Partial loading condition with sloshing effects. Linear, nonlinear mooring stiffness, failure condition. Uncertainty analysis due to viscous effects.